BMP2 signalling activation enhances bone metastases of non‐small cell lung cancer - Huang, Fei (J Cell Mol Med, 2020)
Distant metastases occur when non‐small cell lung cancer (NSCLC) is at late stages. Bone metastasis is one of the most frequent metastases of NSCLC and leads to poor prognosis. It has been reported that high expression of BMP2 in NSCLC correlates with poor survival, but whether BMP2 contributes to NSCLC bone metastasis remains largely unknown. The activation of BMP signalling is found in metastatic bone tumours of mice Lewis lung carcinoma and predicts poor survival in human NSCLC. BMP2 signalling activation can enhance bone metastasis of Lewis lung carcinoma. Moreover, BMP2 secreted by stroma fibroblasts can promote the migration and invasion of NSCLC cells. Besides, in combination with pre‐osteoblast and LLCs, BMP2 could enhance the differentiation of macrophages into osteoclasts to play roles in the osteolytic mechanism of NSCLC bone metastasis. Interestingly, NSCLC cells can also enrich BMP2 to pre‐osteoblasts to function in the osteoblastic mechanism. Our results firstly demonstrate the detailed mechanisms about what roles BMP2 signalling play in enhancing NSCLC bone metastases. These findings provide a new potential therapy choice for preventing bone metastases of NSCLC via the inhibition of BMP2 signalling.